Therapeutic Potential of Nutritional Aryl Hydrocarbon Receptor Ligands in Gut-Related Inflammation and Diseases - Fu-Chen Huang (Biomedicines)
A solid scientific foundation is required to build the concept of personalized nutrition developed to promote health and a vision of disease prevention. Growing evidence indicates that nutrition can modulate the immune system through metabolites, which are either generated via microbiota metabolism or host digestion. The aryl hydrocarbon receptor (AhR) plays a crucial role in regulating immune responses, particularly in the gut, and has emerged as a key modulator of gut-mediated inflammation and related diseases. AhR is a ligand-activated transcription factor that responds to environmental, dietary, and microbial-derived signals, influencing immune balance and maintaining intestinal homeostasis. Nutritional AhR ligands play a significant role in modulating intestinal immunity and the function of mucosal immune cells, thereby exerting clinical effects on colitis and innate immunity. Additionally, they have the capacity to orchestrate autophagy, phagocytic cell function, and intestinal epithelial tight junctions. Therapeutic strategies aimed at enhancing AhR activity, restoring gut integrity, and optimizing immune responses hold promise as avenues for future research and potential treatments for critically ill patients.